ANALISIS KEBEBASAN BERPENDAPAT TERHADAP AGAMA MENURUT PASAL 156A KUHP (STUDI KASUS PUTUSAN NOMOR 784/PID/2018/PT.MDN) - Livianto Sanjaya; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Meliana was charged with violating Article 156a of the Indonesian Criminal Code and was sentenced by a Medan District Court judge with 18 months in prison for being considered a religious blasphemy for complaining about the volume of the call to prayer near her home. The problem is how freedom of expression relates to religion according to Article 156a of the Criminal Code. The research method used in writing this thesis is normative legal research. The results showed that the Medan District Court Judge considered that the element of "blasphemy" was fulfilled by the fact that based on the conversation delivered by witnesses at the trial and there was a very real relationship between the complaints of the defendant and the anger of Muslims and the Fatwa of the Indonesian Ulema Council of North Sumatra Province stated that The defendant is blasphemous towards Islam, which is the religion of Islam adopted in the State of Indonesia. Freedom of opinion is not free freedom, but freedom that is limited by applicable regulations (Law). This case shows that the blasphemy law is actually a tool of conflict, not a conflict prevention as the government considers it. If this law is not abolished, then there must be a way for the law to "no longer be used." Law enforcement officials truly understand the essence of the blasphemy law, so as not to set a bad precedent in the midst of national pluralism.